Electrolyte design for rechargeable magnesium batteries -Methoxyethyl-amine chelants as electrolyte additives - Wilske, Lova (My University, 2022)
Rechargeable magnesium batteries (RMBs) have been pointed out as promising candidates for future electrical energy storage and conversion system due to high theoretical volumetric energy density, low tendency of Mg metal anode to form dendrites, and the high abundance of Mg in the Earth’s crust. Today’s RMBs, however, suffer from low coulombic efficiencies and poor cycle life. Finding suitable electrolytes is the key to overcome these issues. A recently discovered family of electrolyte additives, methoxyethyl-amine chelants, has shown to improve battery performance by providing Mg2+ ion selective first solvation shells. This thesis aims to further explore the properties of these additives by evaluating their compatibility and performance with other electrolyte components and electrode materials, study the imposed morphology of deposits, and conduct EIS analysis to gain insight to the transport properties. Galvanostatic cycling experiments show that 2-methoxyethyl-amine (M3) and 1- methoxy-2-propylamine (M4) increase the coulombic efficiency and lowers overpotential for 0.5 M Mg(TFSI)2:glyme systems. Mean Coulombic efficiencies up to 97% for first 100 cycles were recorded for Mg||SS cells. The additive also displays good performance with the organic cathode material PAQS-CNT. Best performance is achieved with electrolytes with a 1:6 molar ratio between the Mg2+ ions and the additive. Surprisingly, these electrolytes separate into two immiscible phases. Mg metal deposits formed in the presence of the additive are generally larger and exhibit higher Mg purity as shown by SEM and EDS analysis. This indicates that the additive suppresses side reactions and imposes good ion transport at the electrode surface. The very same conclusion was drawn from the EIS analysis, where the interfacial impedance was found to be remarkably low for electrolytes containing the additive.